2021
DOI: 10.1123/jpah.2020-0876
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Stool Metabolite Relationships Among Adults at High Risk for Colorectal Cancer

Abstract: Background: Adenomatous polyps are associated with an increased risk of developing colorectal cancer. Physical activity (PA) and spending less time sedentary may reduce risk of polyp recurrence and cancer incidence. This study examined associations between PA, sedentary time, and stool metabolites in adults at high risk for developing colorectal cancer. Methods: Participants were ≥18 years old with ≥1 adenomatous polyps removed in the previous 3 years. PA and sedentary time were assessed using an activPAL™ acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…Our previous analyses suggest that although activity levels remained unchanged after physical activity education and the combined rice bran + navy bean dietary intervention, stool BAs and SCFAs were cross-sectionally associated with physical activity within this cohort independent of fiber intake ( 47 , 49 ). To our knowledge, this is the first analysis of changes in BAs and SCFAs after a combined rice bran + navy bean intervention.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Our previous analyses suggest that although activity levels remained unchanged after physical activity education and the combined rice bran + navy bean dietary intervention, stool BAs and SCFAs were cross-sectionally associated with physical activity within this cohort independent of fiber intake ( 47 , 49 ). To our knowledge, this is the first analysis of changes in BAs and SCFAs after a combined rice bran + navy bean intervention.…”
Section: Discussionmentioning
confidence: 71%
“…Stool metabolite extraction and targeted BA and SCFA quantification was performed at the Colorado State University Analytical Resources Core: Bioanalysis and Omics facility. Ultrahigh-performance liquid chromatography tandem mass spectrometry was performed for five primary BAs (cholic, taurocholic, glycocholic, chenodeoxycholic, and glycochenodeoxycholic acids) and 12 secondary BAs (deoxycholic, ursodeoxycholic, lithocholic, n u t r i ac h ol i c , 7 al p h a -H y d r o xy -3 -o xo -5 b e t a c ho l a n o i c , hyodeoxycholic, 3-oxocholic, 3alpha,6beta,7beta-Trihydroxy-5bcholanoic, glycodeoxycholic, taurodeoxycholic, 3beta-hydroxy-5cholenoic, and sulfolithocholic acids), following published methods and described below (49). Gas chromatography mass spectrometry (GC-MS) was performed for assessment of six SCFAs (butyric, propionic, isobutyric, isovaleric, valeric, and acetic acids), following published methods described below and are listed in Supplementary Table 1 (49).…”
Section: Targeted Quantification Of Stool Bas and Scfasmentioning
confidence: 99%
“…Also, exercise increased n-butyrate concentrations in the rat cecum [23,[37][38][39]. In human studies, exercise increased fecal acetate, propionate, and butyrate in lean individuals but not in obese ones [24,40]. Thus, exercise-induced short-chain fatty acid concentrations are altered by diet and body size.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate and intense exercise change the composition of gut microbiota and may increase the bacteria diversity [90,149], but no in-depth research has been done on the effect of exercise intensity on gut microbiota. Beale et al found that light intensity exercise correlated with some SCFAs, whereas moderate to vigorous exercise correlated with some BAs [150].…”
Section: The Impact Of Exercise Intensity On Ad and Gut Microbiotamentioning
confidence: 99%